Evolving Remote Laboratory Architectures to Leverage Emerging Internet Technologies - Lowe, D.; Murray, S.; Lindsey, Euan; Liu, Dikai (IEEE Computer Society & IEEE Education Society, 2009)
There is growing research into, and development of, the use of the Internet to support remote access by students to physical laboratory infrastructure. These remote laboratories can, under appropriate circumstances, support or even replace traditional (proximal) laboratories, provide additional or improved access at reduced cost, and encourage interinstitutional sharing of expensive resources. Effective design of remote laboratories requires attention to the design of both the pedagogy and the technical infrastructure, as well as how these elements interact. In this paper, we consider the architectures of remote laboratories, the shortcomings of existing implementations, and we argue that emerging internet technologies can assist in overcoming these shortcomings. We also consider the opportunities which these technologies provide in moving beyond both existing remote laboratories and existing proximal laboratories, to create opportunities which were not previously possible.